Pengembangan Soft Skill Guru - Jaenuri, Jaenuri (Taallum: Jurnal Pendidikan Islam, 2017)
Soft skill is a skill of person that build relationships with others and self-organizing skills. Teachers as a determinant of the potential development of students is not enough can only teach (transfer of knowledge). Moreover, the teacher as a model for the student must have a good personality and social. So teachers are required to develop continuously the ability of personality (intra personal skills) and social skills (inter personal skills). The development of intra personal skills includes: developing the power of consciousness, goals, beliefs, love, concentration, and decisions. The development of interpersonal skills includes: many smiles, appreciative, active listener, active cooperate, mediator, communication ability, humor, empathy, and not easy to complain.